1991
DOI: 10.3168/jds.s0022-0302(91)78324-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rumen Undegradable Protein Levels on Feed Intake and Milk Production of Dairy Cows

Abstract: Twenty-seven dairy cows in midlactation were utilized in two experiments using 15 and 12 cows to determine effects of varying the delivery of ruminally undegraded protein on feed intake, milk production, and some rumen and plasma characteristics. In Experiment 1, cows consumed alfalfa silage ad libitum and one of three barley-based concentrates with either soybean meal (a rapidly rumen degraded protein source), corn gluten meal (a slowly degraded protein source), or an equal mixture of the two, fed at the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 5 publications
0
5
0
4
Order By: Relevance
“…To further research the effect of replacement rate on milk yield, the authors regrouped the studies. The basal diets in those studies were composed principally of corn silage (Cozzi & Polan, 1994;McCormick et al, 2001), oat pasture (McCormick et al, 2001) and alfalfa silage (Robinson et al, 1991). Figure 1 shows no relationship between replacement rate and the change in milk production.…”
Section: Discussionmentioning
confidence: 99%
“…To further research the effect of replacement rate on milk yield, the authors regrouped the studies. The basal diets in those studies were composed principally of corn silage (Cozzi & Polan, 1994;McCormick et al, 2001), oat pasture (McCormick et al, 2001) and alfalfa silage (Robinson et al, 1991). Figure 1 shows no relationship between replacement rate and the change in milk production.…”
Section: Discussionmentioning
confidence: 99%
“…Nianogo et al (1991) reported that lactose content of milk decreased from 4.9% to 4.7% against the control in cows fed diets containing high soluble proteins, and increased from 4.9% to 5.0% against the control in cows fed diets containing less soluble proteins and however, lactose content of milk was not affected by fat addition. Robinson et al (1991) with Maiga and Schingoethe (1997) reported that lactose content of milk was not affected by CP degradabilities of the ration or by by-pass protein content of the ration.…”
Section: Resultsmentioning
confidence: 99%
“…Tabela 6 -Valores médios de produção de leite não-corrigida (PL) e corrigida para 3,5% de gordura (PLG), eficiência de utilização de MS (kg leite/kg matéria seca consumida), eficiência de utilização de N (kg N-leite/kg N-ingerido), teores e quantidades de gordura (G) e proteína bruta (PB) do leite, em função dos níveis de proteína bruta no concentrado, coeficientes de variação (CV), probabilidades (P) para os efeitos linear (L) e quadrático (Q) e equações de regressão , 1996;Armentano et al, 1993;Robinson et al, 1991;Robinson & Kennelly, 1988). Para a produção de leite corrigida para 3,5% de gordura, os aumentos foram de 9,74%, ou 1,84 kg/dia, e as produções de gordura e proteína apresentaram incrementos de 0,08 kg/dia e 0,04 kg/dia, respectivamente, entre os níveis 20 e 23% de PB na MN do concentrado.…”
Section: Cp (G/day)unclassified
“…De acordo com Robinson et al (1991), quando as taxas de ingestão de MS são altas, vacas lactantes podem consumir dietas com menores concentrações de proteína bruta (PB) e ainda assim manter os requerimentos para proteína metabolizável, tornandose desnecessário o fornecimento de proteína não-degradável no rúmen (PNDR) na dieta. Além disso, quando há maior ingestão de MS, a taxa de passagem pode aumentar, resultando aumento do suprimento de PNDR em razão do menor tempo disponível para degradação no rúmen.…”
Section: Introductionunclassified